Mengembangkan Pendidikan Agama Inklusif sebagai Solusi Pengelolaan Keragaman di Indonesia - Yance Z Rumahuru (JURNAL TERUNA BHAKTI, 2018)
This article discusses the importance of inclusive religious education as an instrument for building and developing a model of contextual religious education in Indonesia. This discussion aims to provide alternative thinking to correct the reality of exclusive religious practices that are thought to be influenced by ways of learning religion in schools that have not been able to change and shape Naradidik's inclusive attitude. From the results of various literature studies, it was found that in addition to the widely commented education politics and religious education system, religious education built on an exclusive paradigm has helped shape attitudes of hatred and intolerance among narrators, which can be used as fertile ground for the growth of radicalism and extremism. It was found that inclusive religious education that pays attention to efforts to build awareness of differences can be an effective model that transforms religious education in the context of this pluralistic society in Indonesia. Inclusive religious education is also a medium of religious learning that can shape the moderate attitude of students. In this regard inclusive religious education can be used as a solution for strengthening attitudes towards other groups outside of their own groups and managing diversity in Indonesia. Abstrak Artikel ini mendiskusikan pentingnya pendidikan agama inklusif sebagai instrumen untuk membangun dan mengembangkan satu model pendidikan agama kontekstual di Indonesia. Pembahasan ini bertujuan memberi pemikiran alternatif untuk mengoreksi realitas praktik keagamaan eksklusif yang diduga turut dipengaruhi oleh cara pembelajaran agama di sekolah yang belum mampu mengubah dan membentuk sikap inklusif naradidik. Dari hasil kajian berbagai literatur ditemuai bahwa selain politik pendidikan dan sistem pendidikan agama di Indonesia yang banyak dikomentari, pendidikan agama yang dibangun dalam paradigma eksklusif telah turut membentuk sikap kebencian dan intoleransi di kalangan naradidik, yang dapat dijadikan lahan subur tumbuhnya gerakan radikalisme dan ekstrimisme. Ditemui bahwa pendidikan agama inklusif yang memberi perhatian pada upaya membangun penyadaran terhadap perbedaan dapat dijadikan model efektif yang mentransformasi pendidikan keagamaan dalam konteks bermasyarakat di Indonesia yang majemuk ini. Pendidikan agama inklusif sekaligus menjadi media pembelajaran agama yang dapat membentuk sikap moderat nara didik. Dalam kaitan ini pendidikan agama inklusif dapat dijadikan salah satu solusi bagi penguatan sikap penerimaan terhadap kelompok lain di luar kelompok sendiri dan pengelolaan keragaman di Indonesia.